The Resistance of Women towards Sexual Terrorism in Eve Ensler’s The Vagina Monologues - Ruruk, Laurencya Hellene Larasati; Rosiandani, Ni Luh Putu (Journal of Language and Literature, 2015)
In this present time, women are still oppressed and considered as the inferior class to men. One of the literary works containing the evidence is The Vagina Monologues by Eve Ensler. The monologues inside it share the experiences of various women who have been physically, mentally, and sexually terrorized. From those experiences of the women in the monologues, this study tries to identify the sexual terrorism that is experienced by each woman in each monologue, and at the same time, tries to examine the resistance of the women towards the sexual terrorism.Men use sexual terrorism as a tool to control women’s autonomy over their own body, sexuality, and reproduction. It occurs to any woman in any situation. Sexual terrorism is there to keep women in the subordinate position. The awareness of the women towards the sexual terrorism triggers their resistance towards it. Each woman experiences different situation of sexual terrorism, therefore their ways of resisting the terror are also varied. Feminism approach is used in this study in order to see the accurate analysis of the condition of the woman in each monologue.Keywords: sexual terrorism, women, resistance